ANALISIS PENGARUH CITRA MEREK, KESADARAN MEREK DAN PERSEPSI KUALITAS TERHADAP KEPUTUSAN PEMBELIAN DENGAN LOYALITAS MEREK SEBAGAI VARIABEL INTERVENING (Studi pada Konsumen Cokelat Delfi di Universitas Diponegoro) - Prahasti, Seilla Anjani Maya; Rahardjo, Susilo Toto (Diponegoro Journal of Management, 2018)
This research is motivated   by  the  tight  competition of  chocolate confectionery brand  in Indonesia. It impact  the brand  performance of  an  Delfi  in the last three  years. This study aimed  to analyze the effect  of  brand  image, brand  awareness and  perceived quality  to consumer purchase decision through  brand  loyalty  as the intervening  variable. This  research was  conducted on  Chocolate  Delfi  consumer  at  Diponegoro  University Semarang.The   sampling  method   used  in  this  research  is  non-probability sampling  with purposive sampling  technique. Samples  were  collected from  100  respondents with  the criteria  of students Diponegoro University and who had ever done purchase transaction of Chocolate  Delfi   more   than   two   times.  The   analysis  method   used  in  this  study  is quantitative method  including validity  and reliability  test, classic assumption test, multiple regression analysis, t test, F test, coefficient determination using SPSS and sobel test.The   result  of  this  research  showed  that  brand   image,  brand   awareness  and perceived  quality  has  positive and  significant  effect   on  cunsumer  purchase  decision. Brand  loyalty  has  positive and  significant  effect   on  consumer purchase decision.  The result of sobel test showed that brand image, brand awareness and perceived quality have indirect effect  on consumer purchase decision through brand loyalty.